Epidemiologic Analysis of Malaria Cases Notified in the Municipality of São Gabriel da Cachoeira, Amazonas, Brazil - Santos, Mirely Ferreira dos; Alves, Cleidiana Manoel (International Journal of Advanced Engineering Research and Science, 2021)
Malaria is one of the main public-health issues in the state of Amazonas. The aim of this study was to carry out an epidemiologic analysis of malaria cases in the municipality of São Gabriel da Cachoeira, Amazonas, from 2014 to 2018. The study is a descriptive, ecological study with secondary data collected in the Malaria Epidemiologic Surveillance Information System. The variables of interest were autochthonous cases of malaria; annual parasite incidence (API); sex; age; race & skin color; years of schooling; and Plasmodium species. The results for the number of positive malaria cases per year were: 4,533 cases (2014); 5,071 cases (2015); 10,415 cases (2016); 12,274 cases (2017); and 15,371 cases (2018). The API for malaria varied from 115.9 to 393.2 cases. In 2014, 2015 and 2016, Plasmodium vivax was associated with 99% of positive cases, in 2017 with 92% and in 2018 with 63%. The results of this study show that there is a need to intensify epidemiologic surveillance measures in order to raise awareness of and prevent malaria. Preventive measures should be implemented constantly and intensified so that the population can be protected from malaria even in areas of the municipality where the disease is not endemic.